¿Qué desafíos presenta el Sínodo de la Amazonía a la teología? Pensar el problema desde los posibles retos al estatuto epistemológico de la teología - Vicente Valenzuela Osorio (Franciscanum, 2021)
The challenges that the Synod of the Amazon presents to theology are worked on the horizon of the question of the epistemological status of theology, based on the use of some metaphors used by the texts of the Synod. This work requires the assumption of a key to intertextual reading and a method that justifies the centrality of metaphors and their dynamic lending in relation to the theological foundation («everything is related», «integral ecology», «indigenous mysticism»). The metaphors used by the synodaldocuments give theology something to think about in relation to its internal constitution. They open the way for it to be understood in a different way. This is the case of: ecclesiology, the proper of theological language, the conversions and attitudes for the work of theology, the place of rituality and the value of the local in relation to the intellectusof the mystery and the deposit of faith, interculturality and synodality, among others.